2022
DOI: 10.1186/s12866-022-02646-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-associations of extended-spectrum ß-lactamase producing (ESBL) or AmpC producing E. coli in small and medium pig farms from Khon Kaen province, Thailand

Abstract: Thailand is undergoing rapid intensification of livestock production where small subsistence farms and medium sized commercial farms coexist. In medium farms, antimicrobials are prescribed by a veterinarian, whereas in small farms antimicrobial use remains largely unsupervised. The impact of these differences as well as other farming practices on the emergence and composition of antimicrobial resistance genes (ARGs) remains largely unknown. We analyzed 363 genomes of extended-spectrum ß-lactamase producing (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Although wastewater treatment plants are available on some swine farms in Thailand, there is no regulation that limits the discharge of AMR bacteria or antimicrobial residues released into the environment. As reported previously, several bacteria resistant to powerful antimicrobial agents such as third generation cephalosporin are isolated from swine feces as well as wastewater from those farms [8][9][10]. The presence of clinically relevant resistant bacteria in food-producing animals threatens the sustainability of animal production and human health and warrants further investigation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although wastewater treatment plants are available on some swine farms in Thailand, there is no regulation that limits the discharge of AMR bacteria or antimicrobial residues released into the environment. As reported previously, several bacteria resistant to powerful antimicrobial agents such as third generation cephalosporin are isolated from swine feces as well as wastewater from those farms [8][9][10]. The presence of clinically relevant resistant bacteria in food-producing animals threatens the sustainability of animal production and human health and warrants further investigation.…”
Section: Introductionmentioning
confidence: 86%
“…Members of the Enterobacteriaceae family, especially Escherichia coli, frequently bear diverse ESBLs [11]. In Thailand, several studies have shown the presence of ESBL producer isolated from food-producing animals [8,10]. Although these studies have indicated the occurrence of ESBL producer circulating in food-producing animal farms, the actual quantity of ESBL producer in wastewater treatment plant in food-producing animal farm is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that proper emphasis on hand hygiene at poultry farms and sensitization about biosecurity management can decrease AMU [43]. Initiatives to better inform farmers and veterinarians on appropriate AMU and farm biosecurity could help reduce AMU on farms [5]. In a study of poultry farms in Belgium, sensitization about biosecurity management with specific advice resulted in a 29% reduction in AMU, as indicated by lower treatment incidences during subsequent audits [32].…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
“…Nevertheless, along with noteworthy benefits, indiscriminate antimicrobial usage (AMU) has been the driver for antimicrobial resistance (AMR) selection, which is continuously threatening the global public and animal health systems [4]. Previous studies have proposed a possible link between AMU in animal farming and the emergence of resistant pathogens that can affect the health of both animals and humans [5,6]. In China in 2013, Zhang et al (2015) observed that after the metabolism of 36 antibiotics with a total usage of 92,700 tons, the total excretion amount was 54,000 tons (84% excreted by animals and 16% by humans), and eventually the emission to the environment was 53,800 tons (46% received by water and 54% to the soil) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation